The LAR Chronicles: Radical Domains of Anima - Synnos, Nicos (My University, 2023)
Radical Domains of Anima The Lab for Animation Research (LAR), housed within the Department of Fine Arts at the Cyprus University of Technology, explores the intersections between animation, filmmaking, and visual art. The LAR Chronicles: Radical Domains of Anima introduces the centre’s evolution through art collaborations, experimental research, and the investigatory practice of making animation artworks. This collection provides breakthrough insights into how visual art communicates with contemporary audiences and cultures through filmic time, space, and topological transformations.